Successful Treatment of Eccrine Porocarcinoma Metastasized to a Cervical Lymph Node with CyberKnife Radiosurgery - Taku Fujimura; Akira Hashimoto; Sadanori Furudate; Yumi Kambayashi; Takahiro Haga; Setsuya Aiba (Case Reports in Dermatology, 2014)
Eccrine porocarcinoma is a rare type of skin cancer that originates from eccrine sweat glands or acrosyringium and mainly occurs in the elderly. In this report, we describe an 85-year-old Japanese woman with eccrine porocarcinoma that metastasized to a cervical lymph node who was cured with CyberKnife radiosurgery. Because our patient had a high risk of perioperative complication, standard surgical therapy with a wide margin was impractical. Our present study suggests the novel possibility of using CyberKnife for the treatment of inoperable metastatic porocarcinoma.